2024
DOI: 10.1111/brv.13042
|View full text |Cite
|
Sign up to set email alerts
|

Triggers, cascades, and endpoints: connecting the dots of coral bleaching mechanisms

Joshua Helgoe,
Simon K. Davy,
Virginia M. Weis
et al.

Abstract: The intracellular coral–dinoflagellate symbiosis is the engine that underpins the success of coral reefs, one of the most diverse ecosystems on the planet. However, the breakdown of the symbiosis and the loss of the microalgal symbiont (i.e. coral bleaching) due to environmental changes are resulting in the rapid degradation of coral reefs globally. There is an urgent need to understand the cellular physiology of coral bleaching at the mechanistic level to help develop solutions to mitigate the coral reef cris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 396 publications
0
4
0
Order By: Relevance
“…However, simultaneous exposure to hydrogen and heat stress prevented the decline in the ETR max observed with heat stress alone in Acropora spp.. As shown in previous studies, a decrease in ETR max can serve as an indicator of damage to the photosystem and thereby a deteriorated health state of the Symbiodiniaceae cells [52,53]. This damage presumably originates from the accumulation of ROS/RNS under heat stress as proposed by the "Oxidative Theory" [20,21,22,54,55]. Our result therefore suggests that molecular hydrogen might have protected the coral holobiont against oxidative damage, thereby preventing a decrease in ETR max .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, simultaneous exposure to hydrogen and heat stress prevented the decline in the ETR max observed with heat stress alone in Acropora spp.. As shown in previous studies, a decrease in ETR max can serve as an indicator of damage to the photosystem and thereby a deteriorated health state of the Symbiodiniaceae cells [52,53]. This damage presumably originates from the accumulation of ROS/RNS under heat stress as proposed by the "Oxidative Theory" [20,21,22,54,55]. Our result therefore suggests that molecular hydrogen might have protected the coral holobiont against oxidative damage, thereby preventing a decrease in ETR max .…”
Section: Discussionmentioning
confidence: 67%
“…Direct actions and strategies are therefore urgently needed to further prevent the rapid degradation of these highly valuable ecosystems thereby gaining time for coral reefs until climate change becomes manageable by global efforts [18]. Shifts in physical and biogeochemical conditions are widely recognized to predominantly induce coral bleaching referring to the loss of the coral's endosymbiotic algae Symbiodiniaceae often representing the main energy source of the coral host [19,20]. Novel approaches could therefore aim to target cascades associated with coral bleaching, particularly those initiated by heat stress, offering a promising approach for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Coral bleaching occurs when the nutritional exchange of the symbiosis is disrupted, resulting in the loss of the Symbiodiniaceae, which is the coral's primary source of nutrition [13][14][15], and can result in mass mortality [11,[16][17][18]. The mechanisms underlying the onset and progression of coral bleaching are complex and a topic of intense scientific study (see a recent review in [19]). Research in the last two decades has demonstrated that oxidative stress [19,20], as well as carbon and nitrogen imbalance can drive dysbiosis and lead to bleaching [19,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the onset and progression of coral bleaching are complex and a topic of intense scientific study (see a recent review in [19]). Research in the last two decades has demonstrated that oxidative stress [19,20], as well as carbon and nitrogen imbalance can drive dysbiosis and lead to bleaching [19,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%